Efficacy and safety of canagliflozin alone or as add‐on to other oral antihyperglycemic drugs in Japanese patients with type 2 diabetes: A 52‐week open‐label study. Issue 2 (25th August 2014) - Inagaki, Nobuya; Kondo, Kazuoki; Yoshinari, Toru; Kuki, Hideki
<x xml:space="preserve">Abstract</x> Canagliflozin, a sodium‐glucose co‐transporter 2 inhibitor, significantly reduced hemoglobin A1c, fasting plasma glucose and body weight in Japanese patients with T2DM when used as monotherapy (100 or 200 mg over 52 weeks) in an open‐label trial. Improvements were apparent by 4 weeks of treatment and were maintained for 52 weeks. Canagliflozin was well tolerated with a low incidence of drug‐related adverse events. <boxed-text content-type="graphic" id="jdi12266-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>